Improvement of work temperature at content printing workstation in publishers and printing CV Grafika Dua Tujuh - Suhardi, Bambang; Addina, Dwinda Asyfi; Astuti, Rahmaniyah Dwi (Pusat Pengajian Pengurusan Teknologi dan Logistik (STML), 2020)
CV. Grafika Dua Tujuh is an industry engaged in publishing and printing books and student worksheets located in Klaten. The average output produced daily is 85.400 books and student worksheets, while the company has a production target of 90.000 books and student worksheets. Based on the results of interviews with workers, the level of production that is not maximal is caused by an uncomfortable working environment. Workers in the production room complained about the condition of a hot work environment so that workers feel easily tired and lack of concentration. To overcome the hot workplace, workers often go to the restroom and they work while holding the hand fan. This condition disturbed their concentration and cause work errors. If this condition is carried out continuously, there will be a lot of lost work time which can cause a decrease in productivity. This study aims to analyze the improvement of working temperature conditions in the production room of CV. Grafika Dua Tujuh.This research was conducted by directly measuring thermal conditions in the entire production room of CV. Grafika Dua Tujuh. Determination of the coordinate point of room temperature measurement is based on SNI: 16-7061-2004. Workload assessment is carried out based on SNI 7269: 2009. The results of the measurement of work climate at the content printing workstation are the values of air temperature, humidity, and wind speed i.e 33.32 °C, 39.9%, and 0 m/s. In addition, Wet Bulb Globe Temperature Index (WBGT) value is obtained which is on the verge of a limit, i.e 29.90 °C for the category of the heavy workload with an allocation of working time of 87.5%. The temperature is above the standard set by the Ministry of Health of the Republic of Indonesia No. 1405 / MENKES / 2002 which sets the temperature in an industrial room ranging from 18 °C - 28 °C. Improvement for working temperature is done by engineering control, namely the installation of a turbine ventilator or exhaust fan.